Por dentro dos contratos comunicativos das revistas femininas populares: identidade e significados identificacionais - Andrade, Maria Vanesse (2015)
This research seeks to examine the identity constructions spread across the print media, reportedly aimed at women of class C and discusses that notions of identity (s) the texts in those media are positioned / run in search of identification with their readership. Therefore, we proceeded to analyze three different popular women's magazines produced by Editora Abril circulating in Brazil between 2013 and 2014. The aim was to discuss how AnaMaria present texts, I am more and Max, are related to the values and feminine references the new contemporary Brazilian middle class. This discussion is relevant because in addition to the popular sport of women's magazine is booming today, the magazine product is constituted as an important object of analysis for the study of identity. The research developed in dialogue with elements of Critical Social Psychology, as theoretical and methodological bases the concept of identity in Anthony's perspective of C. Ciampa and Aluísio F. de Lima; the organization of research in itineraries; the Critical Discourse Analysis (CDA) standard proposed by Fairclough; and theoretical and methodological support of the studies of Aidar Prado on the communications contracts in magazines printed on the assessment of thematic constructions of identity and identificacionais meanings. First the research discusses the segmentation process in the magazine market and the historical conditions that led to the emergence of the popular women's magazines, with special emphasis on the journals analyzed. After presenting the main concepts and methods used, we undertook the analysis of communicative contracts of Abril publications. It is observed that the contracts bring texts devoted to the teaching of the best and suitable models, particularly in relation to the reader and have purchasing power. It was observed that the popular magazines while addressing issues related to the feminine universe, seeking to merge these issues with aspects related to the socioeconomic status of the reader.